The benefits and challenges of interdisciplinary collaborations in arts and health practice - Jensen, Anita (2017)
Arts and health are international fields of practice with stakeholders from various disciplines. It is known that the UK has an established practice of collaboration in the form of interdisciplinary partnerships in arts and health (Clift et al., 2009, White, 2009), whereas in Denmark initiatives exist ad-hoc and there is no such established field (Jensen and Wille, 2015).